Overexpression of mir-135b and mir-210 in mesenchymal stromal cells for the enrichment of extracellular vesicles with angiogenic factors. - Juliana Maíra Freitas Vieira; Laura Nicoleti Zamproni; Camila H C Wendt; Kildare Rocha de Miranda; Rafael Soares Lindoso; Sang Won Han (PLoS ONE, 2022)
Extracellular vesicles (EVs) are known as molecular carriers involved in cell communication and the regulation of (patho)physiological processes. miRNAs and growth factors are the main contents of EVs which make them a good candidate for the treatment of diseases caused by ischemia, but the low production of EVs by a cell producer and a significant variation of the molecular contents in EVs according to the cell source are the main limitations of their widespread use. Here, we show how to improve the therapeutic properties of mesenchymal stromal cell (MSC)-derived EVs (MSC-EVs) by modifying MSCs to enrich these EVs with specific angiomiRs (miR-135b or miR-210) using lentiviral vectors carrying miR-135b or miR-210. MSCs were obtained from the mouse bone marrow and transduced with a corresponding lentivector to overexpress miR-135b or miR-210. The EVs were then isolated by ultracentrifugation and characterized using a flow cytometer and a nanoparticle tracking analyzer. The levels of 20 genes in the MSCs and 12 microRNAs in both MSCs and EVs were assessed by RT‒qPCR. The proangiogenic activity of EVs was subsequently assessed in human umbilical vein endothelial cells (HUVECs). The results confirmed the overexpression of the respective microRNA in modified MSCs. Moreover, miR-135b overexpression upregulated miR-210-5p and follistatin, whereas the overexpression of miR-210 downregulated miR-221 and upregulated miR-296. The tube formation assay showed that EVs from MSCs overexpressing miR-210-5p (EVmiR210) significantly promoted tubular structure formation in HUVECs. A significant increase in angiogenic proteins (PGF, endothelin 1, and artemin) and genes (VEGF, activin A, and IGFBP1) in HUVECs treated with VEmiR210 justifies the better tubular structure formation of these cells compared with that of EVmiR135b-treated HUVECs, which showed upregulated expression of only artemin. Collectively, our results show that the EV cargo can be modified by lentiviral vectors to enrich specific miRNAs to achieve a specific angiogenic potential.